2020
DOI: 10.3390/rs12152392
|View full text |Cite
|
Sign up to set email alerts
|

Use of UAS Multispectral Imagery at Different Physiological Stages for Yield Prediction and Input Resource Optimization in Corn

Abstract: Changes in spatial and temporal variability in yield estimation are detectable through plant biophysical characteristics observed at different phenological development stages of corn. A multispectral red-edge sensor mounted on an Unmanned Aerial Systems (UAS) can provide spatial and temporal information with high resolution. Spectral analysis of UAS acquired spatiotemporal images can be used to develop a statistical model to predict yield based on different phenological stages. Identifying critical vegetation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 57 publications
5
19
1
Order By: Relevance
“…This has led to the discussion whether these inconsistencies should be considered as strengths (Lu et al., 2016; Saberioon et al., 2014) or limitations (Augera et al., 2011) of these technologies. Regardless of the platform, it remains important to differentiate the adequacy of using different vegetation indices (Vis) such as structural indices and indices with and without red‐edge to test their validity of use at different growth stages (Barzin et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This has led to the discussion whether these inconsistencies should be considered as strengths (Lu et al., 2016; Saberioon et al., 2014) or limitations (Augera et al., 2011) of these technologies. Regardless of the platform, it remains important to differentiate the adequacy of using different vegetation indices (Vis) such as structural indices and indices with and without red‐edge to test their validity of use at different growth stages (Barzin et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Zhou et al [18] found that indices from multispectral imagery were correlated (R 2 > 0.7) with rice grain yield at various growth stages. Models using data from different epochs may rely on different vegetation indices and reflectance bands as primary inputs, as found in similar modeling studies of corn [16] and sugar beet [19] yield. A multitemporal approach can also allow for the determination of an optimal timing and growth stage for imagery collection [18,20].…”
Section: Introductionmentioning
confidence: 95%
“…We thus opted for a relatively simple VI threshold to identify vegetation pixels in each plot. Similar to Barzin et al [16], we determined that while a Normalized Difference Vegetation Index (NDVI) threshold is commonly used for soil masking [37,38], it is not capable of producing a consistent result amongst the imagery from varying growth stages using a single threshold value. We used the triangular vegetation index (TVI), because the TVI of the canopy exhibited a limited variation over the cropping season compared to NDVI.…”
Section: Canopy Pixel Segmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Smart and precision farming can improve crop yield and quality with the ability to predict and prevent diseases, providing flexible and efficient solutions, using unmanned vehicles, drones, and sensors that allow constant monitoring of the crop [ 1 ]. Thus, spatio-temporal images acquired with drones can be used to develop statistical models to predict crop yields at different phenological stages [ 2 ]. The implementation of sensors to acquire information about the state of crops for monitoring is common in agriculture.…”
Section: Introductionmentioning
confidence: 99%